2022
DOI: 10.3389/fimmu.2021.767512
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Inflammasomes NLRP1 and NLRP3, Toll-Like Receptors, and Vitamin D Receptor in Synovial Fibroblasts From Patients With Different Types of Knee Arthritis

Abstract: Activated rheumatoid arthritis (RA) synovial fibroblasts (SFs) are among the most important cells promoting RA pathogenesis. They are considered active contributors to the initiation, progression, and perpetuation of the disease; therefore, early detection of RASF activation could advance contemporary diagnosis and adequate treatment of undifferentiated early inflammatory arthritis (EA). In this study, we investigated the expression of nucleotide-binding, oligomerization domain (NOD)-like receptor family, pyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…However, many research advances exist on the correlation between bone marrow lesions, synovitis, and OA ( Pauli et al, 2012 ; Coughlin and Kennedy, 2016 ; O’Neill and Felson, 2018 ). As inflammation is the core of the pathogenesis of OA ( Scanzello, 2017 ), including synovitis, innate immune mechanism, and the inherent inflammation of articular cartilage ( Sakalyte et al, 2021 ), it is the current research hotspot in OA. Furthermore, evidence reveals that the occurrence and development of OA are closely related to an autoimmune mechanism ( Barreto et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, many research advances exist on the correlation between bone marrow lesions, synovitis, and OA ( Pauli et al, 2012 ; Coughlin and Kennedy, 2016 ; O’Neill and Felson, 2018 ). As inflammation is the core of the pathogenesis of OA ( Scanzello, 2017 ), including synovitis, innate immune mechanism, and the inherent inflammation of articular cartilage ( Sakalyte et al, 2021 ), it is the current research hotspot in OA. Furthermore, evidence reveals that the occurrence and development of OA are closely related to an autoimmune mechanism ( Barreto et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory factors are expressed and secreted into the joint fluid, such as TNFα, IL-1α, IL-6, and IL-1β [30]. The pro-inflammatory factors further up-regulate MMP1, MMP7, MMP8, MMP12, and MMP13 expression and activation, accelerating OA progression and obstructing cartilage regeneration and repair [31]. In the current study, the results also confirmed that the IL-13 receptor, IL-20 receptor, Cox2, MMP3, and MMP13 are highly expressed in the TNFα-treated human chondrocytes (Figure 3D).…”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of IL-1 β and IL-18 can result in chronic inflammation-related diseases, including POCD [ 9 , 10 ]. By inactivating the NLRP3 inflammasome in preclinical models, VD3 could attenuate osteoarthritis, periodontitis, and cutaneous inflammation [ 15 , 35 , 36 ]. This study demonstrated that NLRP3 inflammasome was upregulated in the hippocampus of aged mice following tibial fracture surgery and that this process was inhibited by VD3 pretreatments.…”
Section: Discussionmentioning
confidence: 99%